Avoidable deaths and harm due to medical negligence - Milunsky, Aubrey (Henry Stewart Talks, 2019)
Introduction to medical negligence, Importance and frequency, Individual & systemic reasons for negligence, The cost and the causes of negligence, Cognitive psychology, decision-making, bias, critical thinking and clinical reasoning, Responsible authority, Recommendations